Fates of lignin and carbohydrates in Siberian soils - Dao, Thi Thao (Hannover : Institutionelles Repositorium der Leibniz Universität Hannover, 2022)
Permafrost-affected soils contain a huge reservoir of organic matter (OM) which, in the past, was largely persistent against microbial decomposition as consequence of cool and waterlogged conditions in the active layer, and freezing in the permafrost layer. Knowing the composition and degree of decomposition at molecular level of soil organic matter (SOM) is relevant to assess their vulnerability under impacts of climate change. This thesis investigated two major constituents of SOM, lignin and carbohydrates, across a west-east gradient in northern Siberia (longitudinal transect) and along a north-south gradient in western Siberia (latitudinal transect), aiming at identifying their fate once permafrost is thawing. The longitudinal transect included three continuous permafrost sites, from Cherskiy (CH) in north-eastern, Logata (LG) in north-central, and Tazovskiy (TZ) in north-western Siberia, which principally differ in active layer thickness and soil mineralogical properties. The latitudinal transect included all major biomes (tundra, taiga, forest steppe and steppe) from arctic to temperate ecosystems, which vary in mean annual temperature (MAT), mean annual precipitation (MAP), vegetation and soil properties. Lignin-derived phenols and neutral sugars within plant and soil samples at each horizon were analysed by CuO oxidation and trifluoroacetic acid (TFA) extraction methods respectively. Along the longitudinal transect, the stage of lignin degradation, appeared to increase from TZ to CH site. The stronger degradation of lignin and neutral sugars at TZ is supposed to be due to the higher MAT and larger active layer thickness, coinciding with better aeration and/or better mobilization of OM. In addition, the larger contents of Fe and Al (hydr)oxides likely additionally stabilized lignin-derived phenols associated with the mineral phase at these sites. With respect to the latitudinal transect, the stage of lignin degradation appeared to increase from tundra to forest steppe, then decrease to steppe. The ...